2018
DOI: 10.1590/s0100-204x2018000400013
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of zygotic embryos of the Brazilian Green Dwarf coconut

Abstract: The objective of this work was to evaluate rewarming procedures and recovery media for Brazilian Green Dwarf coconut (Cocos nucifera) embryos cryopreserved by vitrification. The rewarming procedures evaluated were: T1, water bath at 38±2°C; and T2, unloading solution consisting of Y3 medium + 1.2 mol L-1 sucrose. The recovery media assessed were: M1, Y3 medium + 45 g L-1 sucrose + 1 mg L-1 gibberellic acid + 1 g L-1 activated charcoal + 2.2 g L-1 Gelrite; and M2, Y3 medium + 60 g L-1 sucrose + 2.2 g L-1 Gelrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Preliminary studies have been published to evaluate the viability of cryopreserved BGD accession by means of electrolytic conductivity and potassium leaching tests (COPELAND-GOMES et al, 2012; however, without regeneration after cryopreservation. Recent studies have shown the feasibility of the vitrification technique for the cryopreservation of BGD zygotic embryos (LEDO et al, 2018). Moreover, regeneration techniques by somatic embryogenesis from plumules are more interesting from the point of view of breeding and conservation of genetic resources because they allow obtaining higher number of plants (NGUYEN et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies have been published to evaluate the viability of cryopreserved BGD accession by means of electrolytic conductivity and potassium leaching tests (COPELAND-GOMES et al, 2012; however, without regeneration after cryopreservation. Recent studies have shown the feasibility of the vitrification technique for the cryopreservation of BGD zygotic embryos (LEDO et al, 2018). Moreover, regeneration techniques by somatic embryogenesis from plumules are more interesting from the point of view of breeding and conservation of genetic resources because they allow obtaining higher number of plants (NGUYEN et al, 2015).…”
Section: Introductionmentioning
confidence: 99%